Comparison of liver function status between home treated and hospital treated SARS-CoV-2 survivors - Alam, Mohammad Masum; Rahman, Matiur; Chowdhury, Indira; Mollah, Forhadul Hoque (International Journal of Research in Medical Sciences, 2022)
Background: SARS-CoV-2 has emerged as one of the greatest challenges faced by the world. There is association of liver injury with SARS-CoV-2 infection indicated by abnormal ALT levels accompanied by altered bilirubin level in blood. The aim of the study was to evaluate the quantitative difference of serum ALT and bilirubin level in home and hospital treated patients. Methods: A cross-sectional study was conducted in the Department of Biochemistry and Molecular Biology, Bangabandhu Sheikh Mujib Medical University, from July 2020 to June 2021. After infection most of the patients with mild symptoms were treated at home but patients with difficulty in breathing and various complications were treated at the hospital. Due to SARS-CoV-2 infection certain derangement of liver enzymes were noticed. Results: This study was planned to evaluate the changes of liver enzymes (ALT) and serum bilirubin after the recovery of SARS-CoV-2 infected patients. The aim of the study was to compare the derangement of serum bilirubin and ALT in home and hospital treated patients. Conclusions: There was no significant difference regarding liver function between these two groups.